Collar GPS Tracking System Using GSM Module for Elephant Detection - FADLI; Alias, Afishah; Mohamad, Nazirah (Enhanced Knowledge in Sciences and Technology, 2024)
Wildlife conservation has emerged as a critical global concern in recent years. Among this wildlife conservation, elephants play a critical role in ecosystem dynamics [1] and are particularly vulnerable to threats such as habitat loss [2], poaching [3], and human-wildlife conflicts[4]. In order to solve the human-elephant conflict, a prototype for collar GPS tracking using GSM module was being developed by connecting Neo-6m GPS module and GSM module SIM900A. SMS notifications will be sent to the designated contacts when the prototype reach certain coverage. These notifications will assist the authorities to act towards the elephants. In future, the collars can interpret the movement patterns and elephant behavior to take precaution.